Are postgraduates ready for research? - Clare Boucher (LILAC: Librarians Information Literacy Annual Conference 2009, 2009)
Without any objective criteria, how well can students assess their Information Literacy (IL) skills and their need of further skills development? Would student self-assessment be more realistic if they used an objective tool designed to measure these skills and provide feedback to help identify training needs? The online Research Readiness Self-Assessment (RRSA) tool (created by staff at Central Michigan University) was chosen. In October 2008, new entry research postgraduates (PhD level) at Swansea University were invited to take the RRSA. 67 students (50%) out of a possible 134 took part. Results were analysed to compare students’ self-perceptions with their actual skill levels. After 4 months, students were asked what training they had attended and how useful RRSA had been in making an assessment of their IL training needs. Records of attendance at IL training sessions for the RRSA group and the non-RRSA group were compared. Survey Monkey was used to conduct a brief evaluation of students experience of RRSA. The response rate was 38%. The majority found RRSA had been useful and went on to attend a greater number of IL training sessions.Students who took RRSA were nearly twice as likely to attend Library Training as those who hadn’t. Students’ self-perception of their Information Literacy skills is not always a reliable basis upon which to determine training needs in this area. Student feedback indicates that RRSA is a useful tool in realistically assessing skills and training needs. Students who took RRSA were nearly twice as likely to attend library training as those who hadn’t. Using RRSA can help to raise awareness of, and attendance at, Information Literacy training sessions for research postgraduates. <!-- google_ad_section_end -->